2015
DOI: 10.1038/srep16562
|View full text |Cite
|
Sign up to set email alerts
|

Training of Working Memory Impacts Neural Processing of Vocal Pitch Regulation

Abstract: Working memory training can improve the performance of tasks that were not trained. Whether auditory-motor integration for voice control can benefit from working memory training, however, remains unclear. The present event-related potential (ERP) study examined the impact of working memory training on the auditory-motor processing of vocal pitch. Trained participants underwent adaptive working memory training using a digit span backwards paradigm, while control participants did not receive any training. Before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 58 publications
4
12
1
Order By: Relevance
“…It is noteworthy that LSVT LOUD did not lead to systematic changes of N1 responses to pitch perturbations. This is in contrast with other studies that have shown decreased N1 responses to pitch perturbations in healthy participants following speech perceptual learning and auditory working memory training (Chen et al, 2015;Li et al, 2015) and individuals with PD following external auditory cueing (Huang et al, 2019), reflecting increased efficiency in the neural encoding of pitch information in auditory feedback (Zatorre et al, 2012). Although we cannot provide specific explanations for the absence of N1 modulation following LSVT LOUD, it may be related to the differences in the training protocol.…”
Section: Neurobehavioral Effects Of Lsvt Loudcontrasting
confidence: 99%
See 1 more Smart Citation
“…It is noteworthy that LSVT LOUD did not lead to systematic changes of N1 responses to pitch perturbations. This is in contrast with other studies that have shown decreased N1 responses to pitch perturbations in healthy participants following speech perceptual learning and auditory working memory training (Chen et al, 2015;Li et al, 2015) and individuals with PD following external auditory cueing (Huang et al, 2019), reflecting increased efficiency in the neural encoding of pitch information in auditory feedback (Zatorre et al, 2012). Although we cannot provide specific explanations for the absence of N1 modulation following LSVT LOUD, it may be related to the differences in the training protocol.…”
Section: Neurobehavioral Effects Of Lsvt Loudcontrasting
confidence: 99%
“…For example, larger N1 and P2 responses were elicited by larger size of pitch perturbations (Behroozmand et al, 2009;Liu et al, 2011b;Scheerer et al, 2013). Training-induced decrease of N1 responses and/or increase of P2 responses to pitch perturbations were also found when healthy participants underwent speech perceptual learning or working memory training (Chen et al, 2015;Li et al, 2015;Guo et al, 2017). Previous findings have shown enhanced vocal and/or P2 responses to pitch perturbations in individuals with PD (Liu et al, 2012;Chen et al, 2013;Huang et al, 2016;Mollaei et al, 2016).…”
Section: Introductionmentioning
confidence: 82%
“…Previous studies concerning aging effects on P2 amplitude showed larger P2 amplitude in younger adults, suggesting deficit in the allocation of processing resources for the evaluation of stimulus significance. Consistently, positive correlation was found between the degree of improvement in WM capacity and the post-pre difference in P2 amplitudes after WM training (Li et al, 2015 ). However, the latency of P2 in the present study did not differ in two groups.…”
Section: Discussionmentioning
confidence: 59%
“…Considering that the hippocampus and amygdala are believed to play a critical role in specific memory processes [Phelps, ], our data provide the first evidence for an interplay between the memory‐related subcortical structures and auditory‐vocal integration. Two recent pitch‐shift studies reported significant correlations between memory dysfunction in AD patients and longer persistence of vocal compensations [Ranasinghe et al, ], and between improved working memory capacity and enhanced cortical P2 responses [Li et al, ]. We therefore speculate that top–down signals from the working memory systems, particularly the prefrontal cortex (PFC) [Chmielewski et al, ], might generate an inhibitory effect on vocal motor control to prevent vocal production from being excessively influenced by auditory signals.…”
Section: Discussionmentioning
confidence: 88%